Development of e-learning resources to enhance the pain education curriculum in physiotherapy programs using an action research-guided approach - Mathew, Jerin; Rashid, Muhammed; Shirsath, Priyanka; Raja, Kavitha (Frontiers in Education, 2025)
IntroductionAmong healthcare professionals, Physiotherapists (PTs) are important members of pain management teams and are often the first contact clinicians. PTs must stay informed about the latest advancements in pain management to ensure effective practice. India graduates around 15,000 physiotherapy (PT) students annually, with over 20,000 PTs working in various institutions. However, the current pain curriculum needs to be updated, and resources need to be aligned with internationally accepted standards to improve the PT pain education program.MethodsA three-phase action research methodology (nominal group technique process) was adapted to identify gaps in pain science within the PT curricula of 30 universities in India. Experts used consensus methods to develop e-learning resources (Online and Instructional Digital Versatile Disks; DVDs) to address the gaps in curricula, following the IASP Curriculum Outline on Pain for Physical Therapy.ResultsA total of 22 h of pain lectures were recorded, and four DVDs were produced and duplicated for distribution. These DVDs were mailed to all universities and 469 individual institutions, with a recommendation for integration into undergraduate and postgraduate curricula. The lecture series was made freely accessible online through the institutional library repository.ConclusionWe employed an innovative method for content development based on the IASP curriculum, which involved consulting with experts and undergoing external peer review, leading to the development of e-learning resources. This project has initiated a ripple effect by providing evidence-based knowledge to young therapists and teaching faculty, with e-learning resources and materials readily accessible online. The resources created through this project could support ongoing pain management education for academic professionals and practicing PTs. This could facilitate evidence-based clinical practice and improve patient care.